Petrographical and mineralogical investigation of the rocks of the Bushveld Igneous complex in the Tauteshoogte-Roossenekal area of the Eastern Transvaal - Snyman, C.P. (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 1971.